A skin-friendly, stain-resistant, and wear-resistant composite material, as well as its preparation method and application
The composite material prepared through a specific ratio of raw materials and processes solves the problems of toilet seats having a short-lasting skin-friendly feel, being easily dirty and worn, and having low heat transfer efficiency, and provides a smart toilet seat solution that is soft, stain-resistant, wear-resistant, and has high heat transfer.
Patent Information
- Application Number
- CN202310880294.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-09-30
- Estimated Expiration
- 2043-07-18
AI Technical Summary
Existing toilet seat materials are hard and have a poor touch, making it difficult to provide a soft, delicate and stain-resistant skin-friendly experience. At the same time, the heat transfer efficiency is low, and the stain resistance performance deteriorates after adding thermal conductive agents.
Vinyl polysiloxane, polypropylene, insulating thermal conductor, silane coupling agent, hydrogenated polysiloxane, platinum catalyst and foaming agent are used as raw materials. A composite material is prepared through dynamic vulcanization and foaming process to form a sea-island structure, which is then combined with the overmolding process to prepare the toilet seat.
It achieves a soft, delicate and smooth skin-friendly effect, has good stain resistance and wear resistance, and at the same time improves heat transfer efficiency, and is suitable for smart toilet seat covers.
Smart Images

Figure BDA0004344309900000081 
Figure BDA0004344309900000141 
Figure BDA0004344309900000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a skin-friendly, stain-resistant, and wear-resistant composite material, and a preparation method and application thereof. Background Art
[0002] Currently, toilet seats are primarily made of hard plastic, using injection molding or compression molding. Injection molding primarily uses thermoplastic materials such as polypropylene (PP) and acrylonitrile-butadiene-styrene (ABS) under high temperature and high pressure, while compression molding primarily uses thermosetting urea-formaldehyde (UF) resin under high temperature and high pressure. Existing toilet seats are hard, cold, and have a poor surface feel, easily sticking to the skin and resulting in a poor user experience.
[0003] With the continuous improvement of living standards, people have higher and higher requirements for the toilet experience, especially the skin-friendly feel of toilet seats. They hope that the seats are soft, smooth and elastic, and feel as delicate and smooth as baby skin, and as thin, thick and plump as petals.
[0004] In order to meet the user's demand for skin-friendly feel, the current main solution is to process a layer of soft cloth or other elastic sheet according to the size of the hard toilet seat, and stick it on the hard toilet seat with adhesive.
[0005] However, in the process of realizing the embodiments of the present application, the inventors of the present application found that the above technology has at least the following technical problems: (1) Although a certain skin-friendly experience can be obtained after pasting a layer of soft cloth or other elastic sheet, the experience is not long-lasting because the above materials are not resistant to stains and are easy to get dirty, easily breed bacteria, are not wear-resistant, and need to be cleaned or replaced regularly, which increases the cost of use; (2) In order to obtain a skin-friendly experience, it is necessary to process a layer of soft cloth or other elastic sheet on the surface of the hard toilet seat, which increases the overall thickness of the toilet seat, makes the heat transfer efficiency of the toilet seat low and time-consuming, and is very unsuitable for use in smart toilet heating seats; in order to improve the thermal conductivity of the smart toilet heating seat, a thermal conductor is generally added, and the addition of the thermal conductor will deteriorate the stain resistance of the material.
[0006] Therefore, providing a composite material that has a soft, delicate, smooth and elastic skin-friendly effect, good stain resistance and wear resistance, and high heat transfer efficiency has become a technical problem that needs to be solved urgently in this field. Summary of the Invention
[0007] In order to make up for the defects of the existing technology, the present invention provides a skin-friendly, stain-resistant and wear-resistant composite material and its preparation method and application, which solves the technical problems in the existing technology and realizes that the composite material has a soft, delicate, smooth and elastic skin-friendly effect, and at the same time has good stain resistance and wear resistance, and high heat transfer efficiency, and is suitable for the preparation of toilet seat rings.
[0008] The technical problem to be solved by the present invention is achieved through the following technical solutions:
[0009] The first aspect of the present invention provides a skin-friendly, stain-resistant and wear-resistant composite material, which is prepared by dynamic vulcanization and foaming of raw materials including the following parts by weight: 25-40 parts of vinyl polysiloxane, 45-55 parts of polypropylene, 5-25 parts of insulating thermal conductor, 3-10 parts of silane coupling agent, 5-15 parts of hydrogen-containing polysiloxane, 2-5 parts of platinum catalyst, and 3-8 parts of foaming agent.
[0010] Furthermore, the vinyl content of the vinyl polysiloxane is 0.2-1.0 wt %, and the viscosity at 25° C. is 3000-8000 mPa.s; the hydrogen content of the hydrogen-containing polysiloxane is 0.1-1 wt %.
[0011] Furthermore, the polypropylene is in powder form, with a particle size of 1000-2500 meshes, and a melt index of 20-40 g / 10 min.
[0012] Furthermore, the insulating thermal conductor is aluminum nitride or boron nitride.
[0013] Furthermore, the silane coupling agent is at least one of dimethyldiethoxysilane, dimethyldimethoxysilane, dimethylcyclosiloxane, and hexamethyldisilazane.
[0014] Furthermore, the platinum catalyst is at least one of a chloroplatinic acid tetramethyldivinyldisiloxane complex, a platinum-alkyne complex, and a chloroplatinic acid isopropanol solution, and the content of platinum atoms in the platinum catalyst is 1000 to 2000 ppm.
[0015] Furthermore, the foaming agent is an inorganic foaming agent or an organic foaming agent; the inorganic foaming agent is a carbonate, a bicarbonate or a borohydride; the organic foaming agent is a nitroso compound, an azo compound or a sulfonylhydrazide compound.
[0016] Furthermore, the raw materials also include auxiliary agents; the auxiliary agents include: 1-3 parts of inhibitors.
[0017] Furthermore, the inhibitor is polyvinyl polysiloxane, acetylene alcohol compound, amide compound or cyano compound.
[0018] For alkynol compounds, such as 2-propyn-1-ol, methylbutynol, acetylene cyclohexanol, tert-butyl cyclohexanol, phenylbutynol, 3,5-dimethyl-1-hexyn-3-ol.
[0019] According to another aspect of the present invention, a method for preparing a skin-friendly, stain-resistant, and wear-resistant composite material is provided, comprising the following steps:
[0020] S1. Weigh each raw material according to weight ratio;
[0021] S2, uniformly dispersing vinyl polysiloxane, polypropylene, an insulating thermal conductor, and a silane coupling agent to obtain a mixture A, and mixing and granulating the obtained mixture A to obtain pellets;
[0022] S3, the hydrogen-containing polysiloxane, the platinum catalyst, the foaming agent and the additive are uniformly dispersed to obtain a mixture B;
[0023] S4, feeding the pellets into a twin-screw extruder from a main feed port, feeding the mixed material B into a twin-screw extruder from a side feed port, performing dynamic vulcanization and foaming, and pelletizing by a pelletizer.
[0024] Furthermore, in step S2, vinyl polysiloxane, polypropylene, an insulating thermal conductor and a silane coupling agent are added to a kneader, the temperature is raised to 80-120°C, and high-speed stirring is performed for 30-50 minutes to obtain a mixture A; the mixture A is added to an internal mixer, the temperature is raised to 170°C and mixed evenly, and then extruded and granulated through a single-screw extruder to obtain pellets, wherein the screw processing temperature is 185°C and the speed is 350-500rpm.
[0025] Furthermore, in step S3, hydrogen-containing polysiloxane, platinum catalyst, inhibitor, and foaming agent are added to a high-speed mixer and stirred at room temperature for 10-20 minutes to obtain a mixture B.
[0026] Furthermore, in step S4, the screw processing temperature is 180-200° C. and the screw rotation speed is 400-600 rpm.
[0027] According to another aspect of the present invention, there is provided a use of the above-mentioned skin-friendly, stain-resistant, and wear-resistant composite material in the preparation of a toilet seat.
[0028] According to another aspect of the present invention, a smart toilet seat is provided, which includes a toilet seat bottom layer and a toilet seat surface layer, wherein the toilet seat surface layer is made of the above-mentioned skin-friendly, stain-resistant and wear-resistant composite material and is connected to the toilet seat bottom layer by injection molding.
[0029] Furthermore, the thickness of the bottom layer of the toilet seat is 1.5-2.5 mm, and the thickness of the surface layer of the toilet seat is 3-5 mm.
[0030] Furthermore, the bottom layer of the toilet seat is formed by thermoplastic material through high temperature and high pressure molding.
[0031] Furthermore, the parameters of the injection molding process of the toilet seat surface layer include: melt temperature of 180-210°C, barrel front section temperature of 180-210°C, middle section temperature of 185-210°C, rear section temperature of 180-215°C, mold temperature of 30-60°C, injection screw speed of 50-100 rpm, and injection pressure of 0.5-1.5 MPa.
[0032] The present invention has the following beneficial effects:
[0033] The skin-friendly, stain-resistant and wear-resistant composite material provided by the present invention is prepared by using vinyl polysiloxane, polypropylene, insulating thermal conductor, silane coupling agent, hydrogen-containing polysiloxane, platinum catalyst, and foaming agent in a specific ratio as raw materials through a dynamic vulcanization and foaming process. The raw materials are compatible with each other and act synergistically. The prepared composite material has a soft, delicate, smooth and elastic skin-friendly effect, good stain resistance and wear resistance, and high heat transfer efficiency. It is suitable for preparing smart toilet seat rings, can meet the special requirements of smart toilet seat ring materials, and has a good application market.
[0034] The technical solution of this application is to solve the above technical problems, and the overall idea is as follows:
[0035] The inventors found that the existing toilet seat with a skin-friendly feel is made by processing a layer of soft cloth or other elastic sheet according to the size of the hard toilet seat, and sticking it on the hard toilet seat with adhesive. After sticking a layer of soft cloth or other elastic sheet, although a certain skin-friendly experience can be obtained, the experience is not long-lasting because the above materials are not resistant to stains and are easy to get dirty, easily breed bacteria, are not wear-resistant, and need to be cleaned or replaced regularly, which increases the cost of use. In order to overcome this defect, the composite material of the present application specifically uses vinyl polysiloxane, polypropylene, silane coupling agent, hydrogen-containing polysiloxane, platinum catalyst, and foaming agent as raw materials, adopts dynamic vulcanization process and foaming process, blends unvulcanized vinyl polysiloxane with non-vulcanizable polypropylene under high temperature and high shear, and realizes vulcanization reaction through hydrosilylation reaction. During the process of vulcanization and shearing, the vulcanized rubber is dispersed in the polypropylene, presenting a unique sea-island structure with silicone rubber phase as dispersed phase and polypropylene phase as continuous phase. The obtained foamed silicone rubber TPV has a soft, delicate, smooth and elastic skin-friendly effect, and has good stain resistance and wear resistance. However, the toilet seat surface layer formed by the composite material is compounded on the hard toilet seat bottom layer, which makes the heat transfer efficiency of the toilet seat low and time-consuming. In order to overcome this defect and improve the thermal conductivity of the smart toilet heating seat, the present application adds an insulating thermal conductor. However, the inventors discovered in practice that while adding an insulating thermal conductive agent improves the thermal conductivity of the material, it also degrades the material's stain resistance. To address this technical problem, the inventors conducted further research and discovered that by optimizing the ratio of vinyl polysiloxane to polypropylene, they could significantly mitigate the deterioration of the material's stain resistance caused by the thermal conductive agent.
[0036] The preparation method of the present invention has simple process, easily controllable conditions, low cost, low requirements on equipment, and is suitable for industrial production. DETAILED DESCRIPTION
[0037] It should be noted that the present invention is not limited to the following examples. The methods described are conventional methods unless otherwise specified. The raw materials described can be obtained from public commercial channels unless otherwise specified.
[0038] Unless otherwise specified, the meanings of the terms in this specification are the same as those generally understood by those skilled in the art. However, if there is any conflict, the definitions in this specification shall prevail.
[0039] As used herein, "comprises," "includes," "contains," "has," "having," or other variations thereof are intended to encompass non-exclusive inclusions, and no distinction is made between these terms. The term "comprising" means that other steps and ingredients that do not affect the end result may be added. The term "comprising" also encompasses the terms "consisting of" and "consisting essentially of." The compositions and methods / processes of the present invention comprise, consist of, and consist essentially of the essential elements and limitations described herein, as well as any additional or optional ingredients, components, steps, or limitations described herein.
[0040] All numerical values or expressions used in the specification and claims relating to component amounts, process conditions, etc. should be understood to be modified by "about" in all cases. All ranges relating to the same component or property include endpoints, which can be independently combined. Since these ranges are continuous, they include every numerical value between the minimum and maximum values. It should also be understood that any numerical range cited in this application is intended to include all subranges within that range.
[0041] In the first aspect, a skin-friendly, stain-resistant and wear-resistant composite material is provided, which is prepared by dynamic vulcanization and foaming of raw materials including the following parts by weight: 25-40 parts of vinyl polysiloxane, 45-55 parts of polypropylene, 5-25 parts of insulating thermal conductor, 3-10 parts of silane coupling agent, 5-15 parts of hydrogen-containing polysiloxane, 2-5 parts of platinum catalyst, and 3-8 parts of foaming agent.
[0042] The skin-friendly, stain-resistant and wear-resistant composite material provided by the present invention is prepared by using vinyl polysiloxane, polypropylene, insulating thermal conductor, silane coupling agent, hydrogen-containing polysiloxane, platinum catalyst, and foaming agent in a specific ratio as raw materials through a dynamic vulcanization and foaming process. The raw materials are compatible with each other and act synergistically. The prepared composite material has a soft, delicate, smooth and elastic skin-friendly effect, good stain resistance and wear resistance, and high heat transfer efficiency. It is suitable for preparing smart toilet seat rings, can meet the special requirements of smart toilet seat ring materials, and has a good application market.
[0043] Vinyl polysiloxane
[0044] In the embodiment of the present invention, the weight portion of the vinyl polysiloxane is 25-40 parts, for example, 25 parts, 30 parts, 35 parts, 40 parts and any value therebetween.
[0045] In the embodiment of the present invention, the vinyl content of the vinyl polysiloxane is 0.2-1.0 wt %, and the viscosity at 25° C. is 3000-8000 mPa.s.
[0046] Polypropylene
[0047] Polypropylene is a thermoplastic resin made by polymerizing propylene. Its high crystallinity and regular structure give it excellent mechanical properties. It also possesses excellent heat resistance, chemical stability, and electrical insulation properties.
[0048] In the embodiment of the present invention, the weight proportion of polypropylene is 45-55 parts, such as 45 parts, 48 parts, 50 parts, 52 parts, 55 parts and any value therebetween.
[0049] In the embodiment of the present invention, the polypropylene is in powder form with a particle size of 1000-2500 mesh, and the melt index of the polypropylene is 20-40 g / 10 min.
[0050] Insulating thermal conductive agent
[0051] In an embodiment of the present invention, the weight proportion of the insulating thermal conductor is 5-25 parts, for example, 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 25 parts and any value therebetween.
[0052] In an embodiment of the present invention, the insulating thermal conductor is aluminum nitride or boron nitride.
[0053] In this invention, an insulating thermal conductive agent is added to improve the thermal conductivity of the heated seat of a smart toilet. However, the inventors discovered that while the addition of the thermal conductive agent improves the thermal conductivity of the material, it also degrades its stain resistance. To address this technical problem, the inventors conducted further research and discovered that by optimizing the ratio of vinyl polysiloxane to polypropylene, they could significantly mitigate the degradation of the material's stain resistance caused by the thermal conductive agent.
[0054] Silane coupling agent
[0055] In the embodiment of the present invention, the weight portion of the silane coupling agent is 3-10 parts, for example, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 10 parts and any value therebetween.
[0056] The present invention is not particularly limited to the silane coupling agent. Any silane coupling agent known to those skilled in the art can be used. It can be prepared using a well-known method or purchased commercially. Preferably, the silane coupling agent is at least one of dimethyldiethoxysilane, dimethyldimethoxysilane, dimethylcyclosiloxane, and hexamethyldisilazane.
[0057] The present invention reduces the interfacial tension between the two types of polymers by adding a silane coupling agent, improves the compatibility of silicone rubber and polypropylene, and makes the final product present good performance.
[0058] Hydrogenated polysiloxane
[0059] In the embodiment of the present invention, the weight portion of the hydrogen-containing polysiloxane is 5-15 parts, for example, 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, and any value therebetween.
[0060] The present invention has no particular limitation on the hydrogen-containing polysiloxane, and any hydrogen-containing polysiloxane known to those skilled in the art can be used, and can be prepared using a well-known method or purchased commercially. In the embodiment of the present invention, the hydrogen-containing polysiloxane has a hydrogen content of 0.1-1 wt%.
[0061] Platinum catalyst
[0062] In the embodiment of the present invention, the weight portion of the platinum catalyst is 2-5 parts, for example, 2 parts, 3 parts, 4 parts, 5 parts and any value therebetween.
[0063] In an embodiment of the present invention, the platinum catalyst is at least one of a chloroplatinic acid tetramethyldivinyldisiloxane complex, a platinum-alkyne complex, and a chloroplatinic acid isopropanol solution, and the content of platinum atoms in the platinum catalyst is 1000-2000 ppm.
[0064] foaming agent
[0065] In the embodiment of the present invention, the weight portion of the foaming agent is 3-8 parts, for example, 3 parts, 4 parts, 6 parts, 8 parts and any value therebetween.
[0066] The present invention has no particular limitations on the foaming agent, and any known foaming agent used in the preparation of thermoplastic foam materials familiar to those skilled in the art can be used. It can be prepared using well-known methods or purchased commercially. Preferably, the foaming agent is an inorganic foaming agent or an organic foaming agent; the inorganic foaming agent is a carbonate, bicarbonate, or borohydride; the organic foaming agent is a nitroso compound, an azo compound, or a sulfonylhydrazine compound. Specifically, the nitroso compound can be N,N-dinitrosopentamethylenetetramine (DPT) or N,N-dimethyl-N,N-diterephthalamide (NTA); specifically, the azo compound can be azodicarbonamide (ADC), diisopropyl azodicarboxylate, diethyl azodicarboxylate, or barium azodicarboxylate; preferably, azodicarbonamide. The sulfonylhydrazide compound J can specifically be 4,4-disulfonylhydrazide diphenyl ether (OBSH), p-toluenesulfonylhydrazide, 3,3-disulfonylhydrazide diphenyl sulfone, 4,4-diphenyldisulfonylhydrazide, 1,3-phenyldisulfonylhydrazide, or 1,4-phenyldisulfonylhydrazide.
[0067] The composite material of the present application is foamed while being dynamically vulcanized. The inventor unexpectedly discovered that these two factors work together to significantly improve the skin-friendly effect and stain resistance of the material.
[0068] In addition to the above components, an appropriate amount of auxiliary agent may be added, including but not limited to 1-3 parts of inhibitor.
[0069] The inhibitor is a polyvinyl polysiloxane, an acetylenic alcohol compound, an amide compound, or a cyano compound. The acetylenic alcohol compound includes 2-propyn-1-ol, methyl butynol, acetylene cyclohexanol, tert-butyl cyclohexanol, phenyl butynol, and 3,5-dimethyl-1-hexyn-3-ol.
[0070] In a second aspect, a method for preparing a skin-friendly, stain-resistant, and wear-resistant composite material is provided, comprising the following steps:
[0071] S1. Weigh each raw material according to weight ratio;
[0072] S2, uniformly dispersing vinyl polysiloxane, polypropylene, an insulating thermal conductor, and a silane coupling agent to obtain a mixture A, and mixing and granulating the obtained mixture A to obtain pellets;
[0073] S3, the hydrogen-containing polysiloxane, the platinum catalyst, the foaming agent and the additive are uniformly dispersed to obtain a mixture B;
[0074] S4, feeding the pellets into a twin-screw extruder from a main feed port, feeding the mixed material B into a twin-screw extruder from a side feed port, performing dynamic vulcanization and foaming, and pelletizing by a pelletizer.
[0075] Furthermore, in step S2, vinyl polysiloxane, polypropylene, an insulating thermal conductor and a silane coupling agent are added to a kneader, the temperature is raised to 80-120°C, and high-speed stirring is performed for 30-50 minutes to obtain a mixture A; the mixture A is added to an internal mixer, the temperature is raised to 170°C and mixed evenly, and then extruded and granulated through a single-screw extruder to obtain pellets, wherein the screw processing temperature is 185°C and the speed is 350-500rpm.
[0076] Furthermore, in step S3, hydrogen-containing polysiloxane, platinum catalyst, inhibitor, and foaming agent are added to a high-speed mixer and stirred at room temperature for 10-20 minutes to obtain a mixture B.
[0077] Furthermore, in step S4, the screw processing temperature is 180-200° C. and the screw rotation speed is 400-600 rpm.
[0078] The third aspect provides the application of the above-mentioned skin-friendly, stain-resistant and wear-resistant composite material in the preparation of a smart toilet seat.
[0079] In a fourth aspect, a smart toilet seat is provided, which includes a toilet seat bottom layer and a toilet seat surface layer, wherein the toilet seat surface layer is made of the above-mentioned skin-friendly, stain-resistant and wear-resistant composite material and is connected to the toilet seat bottom layer through injection molding.
[0080] Furthermore, the thickness of the bottom layer of the toilet seat is 1.5-2.5 mm, and the thickness of the surface layer of the toilet seat is 3-5 mm.
[0081] In an embodiment of the present application, the bottom layer of the toilet seat is formed of thermoplastic material through high temperature and high pressure molding.
[0082] The parameters of the injection molding process of the bottom layer of the toilet seat include: melt temperature of 200-230°C, barrel front section temperature of 190-230°C, middle section temperature of 195-230°C, rear section temperature of 190-225°C, mold temperature of 30-60°C, injection screw speed of 60-120 rpm, and injection pressure of 0.3-1.2 MPa.
[0083] The tensile strength of the bottom layer of the toilet seat should be 30-60MPa, the bending strength should be 40-80MPa, and the notched impact strength should be 3.0-20.0kJ / m 2 .
[0084] In an embodiment of the present application, the parameters of the injection molding process of the toilet seat surface layer include: melt temperature of 180-210°C, barrel front section temperature of 180-210°C, middle section temperature of 185-210°C, rear section temperature of 180-215°C, mold temperature of 30-60°C, injection screw speed of 50-100 rpm, and injection pressure of 0.5-1.5 MPa.
[0085] In order to better understand the above technical solution, the above technical solution will be described in detail below with reference to specific examples. The examples are only preferred implementations of the present invention and are not limitations of the present invention.
[0086] The materials of each embodiment and comparative example were prepared according to the formulations listed in Table 1.
[0087] Table 1
[0088]
[0089] Example 1
[0090] A skin-friendly, stain-resistant, and wear-resistant composite material is prepared by dynamic vulcanization and foaming of the following raw materials in parts by weight: 25 parts of vinyl polysiloxane, 45 parts of polypropylene, 5 parts of insulating thermal conductor, 4 parts of silane coupling agent, 5 parts of hydrogen-containing polysiloxane, 2 parts of platinum catalyst, 3 parts of foaming agent, and 1 part of inhibitor.
[0091] The vinyl polysiloxane has a vinyl content of 0.2 wt % and a viscosity of 4000 mPa.s at 25° C.;
[0092] The polypropylene is in powder form with a particle size of 1000-2500 meshes and a melt index of 20 g / 10 min.
[0093] The insulating thermal conductor is aluminum nitride.
[0094] The silane coupling agent is dimethyldiethoxysilane.
[0095] The hydrogen content of the hydrogen-containing polysiloxane is 0.1 wt %.
[0096] The platinum catalyst is a platinum-alkyne complex, and the content of platinum atoms in the platinum catalyst is 1000 ppm.
[0097] The foaming agent is sodium bicarbonate.
[0098] The inhibitor is methylbutynol.
[0099] The preparation method of the skin-friendly, stain-resistant and wear-resistant composite material comprises the following steps:
[0100] S1. Weigh each raw material according to weight ratio;
[0101] S2. Add vinyl polysiloxane, polypropylene, insulating thermal conductive agent, and silane coupling agent to a kneader, raise the temperature to 80° C., and stir at high speed for 30 minutes to obtain a mixture A; add the mixture A to an internal mixer, raise the temperature to 170° C. and mix uniformly, and then extrude and granulate through a single-screw extruder to obtain pellets, wherein the screw processing temperature is 185° C. and the speed is 350 rpm;
[0102] S3. Add hydrogen-containing polysiloxane, platinum catalyst, and inhibitor into a high-speed mixer and stir at room temperature for 10 minutes to obtain mixture B;
[0103] S4, feeding the pellets into a twin-screw extruder from the main feed port, feeding the mixed material B into the twin-screw extruder from the side feed port, performing dynamic vulcanization and foaming, and then pelletizing by a pelletizer; the screw processing temperature is 180° C. and the speed is 400 rpm.
[0104] Example 2
[0105] A skin-friendly, stain-resistant, and wear-resistant composite material is prepared by dynamic vulcanization and foaming of the following raw materials in parts by weight: 30 parts of vinyl polysiloxane, 50 parts of polypropylene, 10 parts of insulating thermal conductor, 3 parts of silane coupling agent, 12 parts of hydrogen-containing polysiloxane, 3 parts of platinum catalyst, 5 parts of foaming agent, and 2 parts of inhibitor.
[0106] The vinyl polysiloxane has a vinyl content of 1.0 wt % and a viscosity of 8000 mPa.s at 25° C.;
[0107] The polypropylene is in powder form with a particle size of 1000-2500 meshes and a melt index of 40 g / 10 min.
[0108] The insulating thermal conductor is boron nitride.
[0109] The silane coupling agent is dimethyldimethoxysilane.
[0110] The hydrogen content of the hydrogen-containing polysiloxane is 1 wt %.
[0111] The platinum catalyst is a chloroplatinic acid isopropanol solution, and the content of platinum atoms in the platinum catalyst is 2000 ppm.
[0112] The foaming agent is azodicarbonamide.
[0113] The inhibitor is acetylene cyclohexanol.
[0114] The preparation method of the skin-friendly, stain-resistant and wear-resistant composite material comprises the following steps:
[0115] S1. Weigh each raw material according to weight ratio;
[0116] S2. Add vinyl polysiloxane, polypropylene, insulating thermal conductive agent, and silane coupling agent to a kneader, raise the temperature to 120° C., and stir at high speed for 50 min to obtain a mixture A; add the mixture A to an internal mixer, raise the temperature to 170° C. and mix evenly, and then extrude and granulate through a single-screw extruder to obtain pellets, wherein the screw processing temperature is 185° C. and the speed is 500 rpm;
[0117] S3. Add hydrogen-containing polysiloxane, platinum catalyst, inhibitor, and foaming agent into a high-speed mixer and stir at room temperature for 20 minutes to obtain mixture B;
[0118] S4, feeding the pellets into a twin-screw extruder from the main feed port, feeding the mixed material B into the twin-screw extruder from the side feed port, performing dynamic vulcanization and foaming, and then pelletizing by a pelletizer; the screw processing temperature is 200° C. and the speed is 600 rpm.
[0119] Example 3
[0120] A skin-friendly, stain-resistant, and wear-resistant composite material is prepared by dynamic vulcanization and foaming of the following raw materials in parts by weight: 40 parts of vinyl polysiloxane, 55 parts of polypropylene, 15 parts of insulating thermal conductor, 10 parts of silane coupling agent, 15 parts of hydrogen-containing polysiloxane, 5 parts of platinum catalyst, 8 parts of foaming agent, and 3 parts of inhibitor.
[0121] The vinyl polysiloxane has a vinyl content of 0.5 wt % and a viscosity of 5000 mPa.s at 25° C.;
[0122] The polypropylene is in powder form with a particle size of 1000-2500 meshes and a melt index of 30 g / 10 min.
[0123] The insulating thermal conductor is aluminum nitride.
[0124] The silane coupling agent is dimethylcyclosiloxane.
[0125] The hydrogen content of the hydrogen-containing polysiloxane is 0.5 wt %.
[0126] The platinum catalyst is a chloroplatinic acid tetramethyldivinyldisiloxane complex, and the content of platinum atoms in the platinum catalyst is 1500 ppm.
[0127] The foaming agent is azodicarbonamide.
[0128] The inhibitor is phenylbutynol.
[0129] The preparation method of the skin-friendly, stain-resistant and wear-resistant composite material comprises the following steps:
[0130] S1. Weigh each raw material according to weight ratio;
[0131] S2. Add vinyl polysiloxane, polypropylene, insulating thermal conductive agent, and silane coupling agent to a kneader, raise the temperature to 90° C., and stir at high speed for 40 min to obtain a mixture A; add the mixture A to an internal mixer, raise the temperature to 170° C. and mix uniformly, and then extrude and granulate through a single-screw extruder to obtain pellets, wherein the screw processing temperature is 185° C. and the speed is 400 rpm;
[0132] S3. Add hydrogen-containing polysiloxane, platinum catalyst, inhibitor, and foaming agent into a high-speed mixer and stir at room temperature for 15 minutes to obtain mixture B;
[0133] S4, feeding the pellets into a twin-screw extruder from the main feed port, feeding the mixed material B into the twin-screw extruder from the side feed port, performing dynamic vulcanization and foaming, and then pelletizing the pellets using a pelletizer; the screw processing temperature is 190° C. and the speed is 500 rpm.
[0134] Example 4
[0135] A skin-friendly, stain-resistant, and wear-resistant composite material is prepared by dynamic vulcanization and foaming of the following raw materials in parts by weight: 30 parts of vinyl polysiloxane, 50 parts of polypropylene, 20 parts of insulating thermal conductor, 4 parts of silane coupling agent, 12 parts of hydrogen-containing polysiloxane, 2 parts of platinum catalyst, 4 parts of foaming agent, and 1 part of inhibitor.
[0136] The vinyl polysiloxane has a vinyl content of 0.6 wt % and a viscosity of 4000 mPa.s at 25° C.;
[0137] The polypropylene is in powder form with a particle size of 1000-2500 meshes and a melt index of 30 g / 10 min.
[0138] The insulating thermal conductor is boron nitride.
[0139] The silane coupling agent is dimethyldiethoxysilane.
[0140] The hydrogen content of the hydrogen-containing polysiloxane is 0.4 wt %.
[0141] The platinum catalyst is a chloroplatinic acid tetramethyldivinyldisiloxane complex, and the content of platinum atoms in the platinum catalyst is 1600 ppm.
[0142] The foaming agent is azodicarbonamide.
[0143] The inhibitor is 2-propyn-1-ol.
[0144] The preparation method of the skin-friendly, stain-resistant and wear-resistant composite material comprises the following steps:
[0145] S1. Weigh each raw material according to weight ratio;
[0146] S2. Add vinyl polysiloxane, polypropylene, insulating thermal conductive agent, and silane coupling agent to a kneader, raise the temperature to 100° C., and stir at high speed for 40 minutes to obtain a mixture A; add the mixture A to an internal mixer, raise the temperature to 170° C. and mix uniformly, and then extrude and granulate through a single-screw extruder to obtain pellets, wherein the screw processing temperature is 185° C. and the speed is 380 rpm;
[0147] S3. Add hydrogen-containing polysiloxane, platinum catalyst, inhibitor, and foaming agent into a high-speed mixer and stir at room temperature for 16 minutes to obtain mixture B;
[0148] S4, feeding the pellets into a twin-screw extruder from the main feed port, feeding the mixed material B into the twin-screw extruder from the side feed port, performing dynamic vulcanization and foaming, and then pelletizing by a pelletizer; the screw processing temperature is 190° C. and the speed is 450 rpm.
[0149] Example 5
[0150] A skin-friendly, stain-resistant, and wear-resistant composite material is prepared by dynamic vulcanization and foaming of the following raw materials in parts by weight: 35 parts of vinyl polysiloxane, 50 parts of polypropylene, 25 parts of insulating thermal conductor, 6 parts of silane coupling agent, 10 parts of hydrogen-containing polysiloxane, 2 parts of platinum catalyst, 4 parts of foaming agent, and 1 part of inhibitor.
[0151] The vinyl polysiloxane has a vinyl content of 1.0 wt % and a viscosity of 8000 mPa.s at 25° C.;
[0152] The polypropylene is in powder form with a particle size of 1000-2500 meshes and a melt index of 25 g / 10 min.
[0153] The thermal conductor is boron nitride with a particle size of 1500-3000 meshes.
[0154] The silane coupling agent is hexamethyldisilazane.
[0155] The hydrogen content of the hydrogen-containing polysiloxane is 0.5 wt %.
[0156] The platinum catalyst is a chloroplatinic acid tetramethyldivinyldisiloxane complex, and the content of platinum atoms in the platinum catalyst is 1000 ppm.
[0157] The insulating thermal conductor is aluminum nitride.
[0158] The inhibitor is 2-propyn-1-ol.
[0159] The preparation method of the skin-friendly, stain-resistant and wear-resistant composite material comprises the following steps:
[0160] S1. Weigh each raw material according to weight ratio;
[0161] S2. Add vinyl polysiloxane, polypropylene, insulating thermal conductive agent, and silane coupling agent to a kneader, raise the temperature to 110° C., and stir at high speed for 35 minutes to obtain a mixture A; add the mixture A to an internal mixer, raise the temperature to 170° C. and mix uniformly, and then extrude and granulate through a single-screw extruder to obtain pellets, wherein the screw processing temperature is 185° C. and the speed is 400 rpm;
[0162] S3. Add hydrogen-containing polysiloxane, platinum catalyst, inhibitor, and foaming agent into a high-speed mixer and stir at room temperature for 18 minutes to obtain mixture B;
[0163] S4, feeding the pellets into a twin-screw extruder from the main feed port, feeding the mixed material B into the twin-screw extruder from the side feed port, performing dynamic vulcanization and foaming, and then pelletizing the pellets using a pelletizer; the screw processing temperature is 180° C. and the speed is 500 rpm.
[0164] Comparative Example 1
[0165] The only difference from Example 4 is that the weight portion of the insulating thermal conductive agent is 0 parts.
[0166] Comparative Example 2
[0167] The only difference from Example 4 is that the weight portion of polypropylene is 25 parts.
[0168] Comparative Example 3
[0169] The only difference from Example 4 is that the weight portion of polypropylene is 70 parts.
[0170] Comparative Example 4
[0171] The only difference from Example 4 is that the weight portion of the foaming agent is 0 part.
[0172] The above embodiments and comparative examples and the prepared composite materials are respectively processed and formed into a toilet seat, which includes a toilet seat bottom layer and a toilet seat surface layer, wherein the toilet seat surface layer is made of the above-mentioned skin-friendly, stain-resistant and wear-resistant composite material and is connected to the toilet seat bottom layer through injection molding.
[0173] The bottom layer of the toilet seat is formed of PP material under high temperature and high pressure; the thickness of the bottom layer of the toilet seat is 2 mm, and the thickness of the surface layer of the toilet seat is 4 mm.
[0174] The parameters of the injection molding process of the bottom layer of the toilet seat include: melt temperature of 200-230°C, barrel front section temperature of 190-230°C, middle section temperature of 195-230°C, rear section temperature of 190-225°C, mold temperature of 30-60°C, injection screw speed of 60-120 rpm, and injection pressure of 0.3-1.2 MPa.
[0175] The parameters of the injection molding process of the toilet seat surface layer include: melt temperature of 180-210°C, barrel front section temperature of 180-210°C, middle section temperature of 185-210°C, rear section temperature of 180-215°C, mold temperature of 30-60°C, injection screw speed of 50-100 rpm, and injection pressure of 0.5-1.5 MPa.
[0176] Performance Testing
[0177] In order to verify the performance of the product of the present invention, the toilet seat covers prepared in each embodiment and comparative example were respectively subjected to relevant performance tests, and the specific methods are as follows:
[0178] (1) Anti-fouling performance test
[0179] Water contact angle test: Tested in accordance with GB / T 30693-2014, "Measurement of the contact angle of water with plastic films." The contact angle is measured using a water contact angle analyzer and used as a basis for evaluating stain resistance. A larger water contact angle indicates better hydrophobicity.
[0180] Oil contact angle test: This test is conducted using n-hexadecane in accordance with GB / T 30693-2014, "Measurement of the Contact Angle of Water with Plastic Films." The contact angle is measured using a water contact angle analyzer and used as a basis for evaluating the sample's anti-fouling properties. A larger oil contact angle indicates better oleophobic properties.
[0181] Anti-fouling performance test: According to GB / T17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels", pollutants such as cola, light soy sauce and ketchup are placed on the surface of the toilet seat for 24 hours, and then cleaned with an organic solvent. The surface appearance, shape, gloss and color of the toilet seat are observed to see if there are any changes. The more severe the changes, the worse the material's pollution resistance; conversely, slight changes or no traces of them indicate better pollution resistance.
[0182] Level 5: No significant changes;
[0183] Grade 4: Slight changes in gloss and / or color;
[0184] Level 3: Moderate changes in gloss and / or color;
[0185] Level 2: There is a noticeable change in gloss and / or color;
[0186] Level 1: Surface deformation and / or blistering.
[0187] (2) Thermal conductivity test
[0188] The thermal conductivity of the toilet seat surface layer was tested in accordance with GB / T 3399-1982 "Test method for thermal conductivity of plastics - Hot plate method".
[0189] (3) Wear resistance test
[0190] The toilet seat surface was tested for abrasion resistance according to GB / T 21996.3-2007, "Textiles - Determination of the Abrasion Resistance of Fabrics by the Martindale Method - Part 3: Determination of Mass Loss." A 795g load was applied, and the surface was rubbed 4000 times. The abrasion resistance index was then calculated.
[0191] Ai=n / Δm
[0192] Where:
[0193] Ai-wear resistance index, unit is times per milligram (times / mg);
[0194] n-total number of frictions, in times;
[0195] Δm-mass loss of the sample under the total number of friction times, in milligrams (mg).
[0196] The larger the Ai value, the better the wear resistance of the product.
[0197] (4) Skin-friendly performance test
[0198] Touch the toilet seat with your hand to see if it feels soft, delicate and smooth. A skin-friendly toilet seat feels very soft, delicate and smooth.
[0199] Sit on the toilet seat with your buttocks to see if it is elastic. A good skin-friendly seat should have moderate elasticity.
[0200] The test results are shown in Table 2 below:
[0201] Table 2
[0202]
[0203]
[0204] It can be seen from Table 2 that the composite material obtained in the embodiment of the present invention has a soft, delicate, smooth and elastic skin-friendly effect, and has good stain resistance and wear resistance, as well as high heat transfer efficiency.
[0205] It can also be seen from Table 2 that, by comparing Comparative Example 1 with Example 4, in Comparative Example 1, since there is no insulating thermal conductor in the raw materials, the thermal conductivity of the toilet seat prepared is significantly poor, but the stain resistance is improved.
[0206] It can also be seen from Table 2 that by comparing Comparative Examples 2-3 with Example 4, Comparative Examples 2-3 contain an insulating thermal conductor, and the dosage ratio of vinyl polysiloxane and polypropylene is not within the scope of the present invention, and the resulting toilet seat has significantly poor stain resistance.
[0207] By comparing Comparative Example 4 with Example 4, under the condition that other conditions remain unchanged, no foaming agent is added in Comparative Example 4, and the skin-friendly effect and anti-fouling performance of the material are greatly reduced.
[0208] The above-mentioned embodiments merely express the implementation methods of the present invention. The description thereof is relatively specific and detailed, but it cannot be understood as limiting the patent scope of the present invention. Any technical solution obtained in the form of equivalent replacement or equivalent transformation should fall within the scope of protection of the present invention.
Claims
1. A skin-friendly, stain-resistant and wear-resistant composite material, characterized in that: The invention is used to prepare an intelligent toilet seat, which is prepared by dynamic vulcanization and foaming of the following raw materials in parts by weight: 25-40 parts of vinyl polysiloxane, 45-55 parts of polypropylene, 5-25 parts of insulating thermal conductor, 3-10 parts of silane coupling agent, 5-15 parts of hydrogen-containing polysiloxane, 2-5 parts of platinum catalyst, and 3-8 parts of foaming agent, wherein the vinyl polysiloxane is unvulcanized vinyl polysiloxane. The raw materials also include auxiliary agents; the auxiliary agents include: 1-3 parts of inhibitor; The preparation method of the skin-friendly, stain-resistant and wear-resistant composite material comprises the following steps: S1. Weigh each raw material according to weight ratio; S2, uniformly dispersing vinyl polysiloxane, polypropylene, an insulating thermal conductor, and a silane coupling agent to obtain a mixture A, and mixing and granulating the obtained mixture A to obtain pellets; S3, the hydrogen-containing polysiloxane, the platinum catalyst, the foaming agent and the additive are uniformly dispersed to obtain a mixture B; S4, feeding the pellets into a twin-screw extruder from a main feed port, feeding the mixed material B into a twin-screw extruder from a side feed port, performing dynamic vulcanization and foaming, and pelletizing by a pelletizer.
2. The skin-friendly, stain-resistant, and wear-resistant composite material according to claim 1, characterized in that: The vinyl content of the vinyl polysiloxane is 0.2-1.0 wt %, and the viscosity at 25° C. is 3000-8000 mPa.s; the hydrogen content of the hydrogen-containing polysiloxane is 0.1-1 wt %.
3. The skin-friendly, stain-resistant, and wear-resistant composite material according to claim 1, characterized in that: The polypropylene is in powder form and has a particle size of 1000-2500 meshes.
4. The skin-friendly, stain-resistant, and wear-resistant composite material according to claim 1, characterized in that: The insulating thermal conductor is aluminum nitride or boron nitride; the silane coupling agent is at least one of dimethyldiethoxysilane, dimethyldimethoxysilane, dimethylcyclosiloxane, and hexamethyldisilazane; the platinum catalyst is at least one of a chloroplatinic acid tetramethyldivinyldisiloxane complex, a platinum-alkyne complex, and a chloroplatinic acid isopropanol solution, and the platinum atom content in the platinum catalyst is 1000 to 2000 ppm; the foaming agent is an inorganic foaming agent or an organic foaming agent; the inorganic foaming agent is a carbonate, a bicarbonate, or a borohydride; and the organic foaming agent is a nitroso compound, an azo compound, or a sulfonylhydrazine compound.
5. The skin-friendly, stain-resistant, and wear-resistant composite material according to claim 1, characterized in that: The inhibitor is an alkynol compound, an amide compound or a cyano compound.
6. A method for preparing the skin-friendly, stain-resistant, and wear-resistant composite material according to any one of claims 1 to 5, comprising the following steps: S1. Weigh each raw material according to weight ratio; S2, uniformly dispersing vinyl polysiloxane, polypropylene, an insulating thermal conductor, and a silane coupling agent to obtain a mixture A, and mixing and granulating the obtained mixture A to obtain pellets; S3, the hydrogen-containing polysiloxane, the platinum catalyst, the foaming agent and the additive are uniformly dispersed to obtain a mixture B; S4, feeding the pellets into a twin-screw extruder from a main feed port, feeding the mixed material B into a twin-screw extruder from a side feed port, performing dynamic vulcanization and foaming, and pelletizing by a pelletizer.
7. Use of the skin-friendly, stain-resistant, and wear-resistant composite material according to any one of claims 1 to 5 in the preparation of an intelligent toilet seat.
8. A smart toilet seat, comprising a toilet seat bottom layer and a toilet seat surface layer, characterized in that: The surface layer of the toilet seat is made of the skin-friendly, stain-resistant and wear-resistant composite material according to any one of claims 1 to 5 and is connected to the bottom layer of the toilet seat through overmolding.
9. The intelligent toilet seat according to claim 8, characterized in that: The bottom layer of the toilet seat has a thickness of 1.5-2.5 mm, and the surface layer of the toilet seat has a thickness of 3-5 mm; the bottom layer of the toilet seat is formed by thermoplastic material through high temperature and high pressure molding.